Geographic Disparities in Mortality Risk Within a Racially Diverse Sample of U.S. Veterans with Traumatic Brain Injury - Clara E. Dismuke-Greer; Mulugeta Gebregziabher; Tiarney Ritchwood; Mary Jo Pugh; Rebekah J. Walker; Uche S. Uchendu; Leonard E. Egede (Mary Ann Liebert, 2018)
Purpose: Traumatic brain injury (TBI) is a signature injury among the U.S. veterans. Hispanic U.S. veterans diagnosed with TBI have been found to have higher risk-adjusted mortality. This study examined the adjusted association of geographic location with all-cause mortality in 114,593 veterans diagnosed with TBI between January 1, 2000 and December 31, 2010, and followed through December 31, 2014. Methods: National Veterans Health Administration (VHA) databases containing administrative data including International Classification of Diseases, 9th Revision (ICD-9) codes, sociodemographic characteristics, and survival were linked. TBI was identified based on ICD-9 codes. Cox proportional hazards regression methods were used to examine the association of time from first TBI ICD-9 code to death with geographic location, after adjustment for TBI severity, race/ethnicity, other sociodemographic characteristics, military factors, and Elixhauser comorbidities. Results: Relative to urban mainland veterans with a median survival of 76.4 months, veterans living in the U.S. territories had a median survival of 69.1 months, whereas rural mainland veterans had a median survival of 77.1 months, and highly rural mainland veterans had a mean survival of 77.6 months. The final model adjusted for race/ethnicity, TBI severity, sociodemographic, military, and comorbidity covariates showed that residing in the U.S. territories was associated with a higher risk of death (hazard ratios=1.24; 95% confidence interval 1.15?1.34) relative to residing on the U.S. mainland. The race/ethnicity disparity previously found for the U.S. veterans diagnosed with TBI seems to be accounted for by living in the U.S. territories. Conclusion: The study shows that among veterans with TBI, mortality rates were higher in those who reside in the U.S. territories, even after adjustment. Previous documented higher mortality among Hispanic veterans seems to be explained by residing in the U.S. territories. The VA has a mission of ensuring equitable treatment of all veterans, and should investigate targeted policies and interventions to improve the survival of the U.S. territory veterans diagnosed with TBI.